Progress towards a Nordic standard for the investigation of hematuria: 2019. (2nd January 2019) - Malmström, Per-Uno; Skaaheim Haug, Erik; Boström, Peter J.; Gudjónsson, Sigidur; Bjerggaard Jensen, Jørgen
Abstract: Objective: To describe the management of patients with hematuria in the Nordic countries in relation to bladder cancer epidemiology, especially in the context of introducing fast track pathways with the aim of proposing a common guideline. Materials and methods: Epidemiological data on bladder cancer from each country, and the combined cancer registry, Nordcan, were analyzed. The evolution of the different national recommendations and the introduction of fast track pathways were assessed. Patients' demographics, type of hematuria and cancer detection rates were analysed if available. Results: The crude incidence of bladder cancer has increased substantially since the 1960s, while the age standardized incidence has been stable during recent decades. The relative survival has increased in all countries, while the mortality has been stable. For those with microscopic hematuria there has been a clear trend towards less rigorous investigations. In the fast track pathways, introduced in three of five countries, about one in five patients with macroscopic hematuria had a cancer diagnosis. Data show that time to diagnosis has been reduced. Conclusions: The number of patients with bladder cancer is increasing in the Nordic region. The introduction of fast track pathways has been important in improving the management of patients with suspicion of the disease. Our recommendation is to focus on macroscopic hematuria in the fast track pathways. Microhematuria without any symptoms should not be an indication for cystoscopy. However, urinary tract symptoms accompanied by microhematuria can still be investigated according to respective guidelines but not necessarily within fast track pathways.